Psychological interventions for post-traumatic stress injuries among public safety personnel: a systematic review and meta-analysis - Anees Bahji; Paula M. Di Nota; Dianne Groll; R. Nicholas Carleton; Gregory S. Anderson (Systematic Reviews, 2022)
Abstract Background Public safety personnel (PSP) are exposed to potentially psychologically traumatic events (PPTE) far more often than the general public, which increases the risk for various post-traumatic stress injuries (PTSIs). While there are many evidence-based psychological interventions for PTSI, the effectiveness of each intervention for PSP remains unclear. Objectives The current study assessed the effectiveness and acceptability of psychological interventions for PTSI among PSPs. Methods A systematic review and random-effects meta-analysis were performed on the effectiveness and acceptability of psychotherapies for PTSIs (i.e., symptoms of depression, anxiety, post-traumatic stress disorder) among PSP. The review adhered to the PRISMA reporting guidelines and used standardized mean differences (Cohen’s d), rate ratios (RR), and their 95% confidence intervals (95% CI) to measure pooled effect sizes across studies; negative d values and RR values less than one indicated a reduction in symptoms compared to baseline or control groups. In addition, heterogeneity was quantified using I 2 , and publication bias was evaluated using Egger’s test. Results The analyses included data from eight randomized controlled trials representing 402 PSP (79.4% male, 35.3 years). Psychological interventions included narrative exposure therapy (n = 1), cognitive behavioral therapy (n = 2), eclectic psychotherapy (n = 2), eye-movement desensitization and reprocessing (n = 1), supportive counseling (n = 2), and group critical incident stress debriefing (n = 1). The interventions were associated with statistically significant reductions in symptoms associated with PTSD (d = − 1.23; 95% CI − 1.81, − 0.65; 7 studies; I 2 = 81%), anxiety (− 0.76; 95% CI − 1.28, − 0.24; 3 studies; I 2 = 47%), and depression (d = − 1.10; 95% CI − 1.62, − 0.58; 5 studies; I 2 = 64%). There were smaller but statistically significant improvements at follow-up for symptoms of PTSD (d = − 1.29 [− 2.31, − 0.27]), anxiety (d = − 0.82 [− 1.20, − 0.44]), and depression (d = − 0.46 [− 0.77, − 0.14]). There were no statistically significant differences in dropout rates (RR = 1.00 [0.96, 1.05]), suggesting high acceptability across interventions. Conclusions There is preliminary evidence that psychotherapies help treat PTSIs in PSP; however, the shortage of high-quality studies on PSP indicates a need for additional research into treating PTSI among PSP. Systematic review registration PROSPERO: CRD42019133534.